Delay Risk Factors in Foundation Works Using SEM and Multi-Group Analysis - Jonathan Natanael; Hans Dermawan; Fenny Septiastuti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Delays in construction projects continue to be a significant problem in infrastructure development, especially in foundation works where field uncertainties are common. This study aims to identify the dominant delay risk factors and examine their influence on project time performance. A quantitative approach was applied using questionnaires distributed to construction professionals, and the collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA). The results indicate that equipment and productivity factors as well as financial and administrative factors have significant effects on project time performance, while other factors were not statistically significant. The structural model showed moderate explanatory power with an R² value of 0.471. The findings also revealed a discrepancy between perceived importance and actual impact, where technical factors were perceived as highly important but operational and financial factors showed stronger direct effects on project execution. In addition, no significant differences were found between contractors and consultants. It was concluded that mitigation strategies should prioritize operational and financial aspects to effectively reduce delays in foundation works.